2017
DOI: 10.1038/onc.2017.254
|View full text |Cite
|
Sign up to set email alerts
|

Mdm2 promotes Cdc25C protein degradation and delays cell cycle progression through the G2/M phase

Abstract: Upon different types of stress, the gene encoding the mitosis-promoting phosphatase Cdc25C is transcriptionally repressed by p53, contributing to p53’s enforcement of a G2 cell cycle arrest. In addition, Cdc25C protein stability is also decreased following DNA damage. Mdm2, another p53 target gene, encodes a ubiquitin ligase that negatively regulates p53 levels by ubiquitination. Ablation of Mdm2 by siRNA led to an increase in p53 protein and repression of Cdc25C gene expression. However, Cdc25C protein levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 80 publications
(100 reference statements)
3
35
0
Order By: Relevance
“…Cdc25C shuttles in and out of the nucleus continuously, just like cyclin B1. Cdc25C will not cause premature mitosis before cyclin B1 overexpress (Karlsson et al, 1999) and cdc25C is a member of the cyclin-dependent kinases of cell cycle-related CDKs (Giono et al, 2017). In the present study, we found that SB induced cell cycle arrest at G2/M phase and reduced the protein expressions of cdc25C, CDK1, and cyclin B1 in cervical cancer cells, which may be the mechanism of action underlying the SB-inhibited cervical cancer cell proliferation.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Cdc25C shuttles in and out of the nucleus continuously, just like cyclin B1. Cdc25C will not cause premature mitosis before cyclin B1 overexpress (Karlsson et al, 1999) and cdc25C is a member of the cyclin-dependent kinases of cell cycle-related CDKs (Giono et al, 2017). In the present study, we found that SB induced cell cycle arrest at G2/M phase and reduced the protein expressions of cdc25C, CDK1, and cyclin B1 in cervical cancer cells, which may be the mechanism of action underlying the SB-inhibited cervical cancer cell proliferation.…”
Section: Discussionsupporting
confidence: 57%
“…In the progression of the cell cycle, members of the CDK family and the partner cyclinproteins are the primary mediators controlling the point of entry into mitosis in cells (Jones et al, 2018). Cyclin B1/CDK1 kinase translocating rapidly from the cytoplasm to the nucleus is the critical target of G2 into mitosis transition (Giono et al, 2017). CDK1 promotes the DNA replicative synthesis and regulates the balance of cell cycle, thus coordinating and maintaining genomic stability, which is vital for cell survival (Liao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Neurofibromatosis Type 2 Protein (NF2) is involved in cell cycle regulation, although it has not been shown to have a direct effect on the cell cycle [36]. Other proteins, including GADD45α, The Aurora Kinase A (AURKA) [37], and Mouse double minute 2 homolog (MDM2) [38], have been shown to regulate cell cycle progression at the G2/M phase. Interestingly, it was reported that induction of GADD45α increased its association with cyclin-dependent kinase 1 (CDK1; also known as cell division cycle protein 2 homolog) and forced it to dissociate from cyclin B1/CDK1 complexes.…”
Section: Discussionmentioning
confidence: 99%
“…But all the noscapine analogues except 4 and 1 decreased the expression of Cdc25C protein, which is necessary for the progression of cell cycle through the G2/M phase. Cdc25C activity inhibition is pivotal for the G2 checkpoint and has been shown that decrease in Cdc25C expression causes cell cycle arrest at G2/M phase . These results demonstrate that noscapine analogues 6 e – g and 6 j result in G2/M phase arrest as indicated by the levels of cell‐cycle regulators cyclin B1, CDK1, Cdc25C.…”
Section: Resultsmentioning
confidence: 99%